REGICIDE AND RESISTANCE IN JOHN GALT’S THE SPAEWIFE: THEMES OF TYRANNY AND LIBERTY (International Journal of Food and Nutritional Sciences, 2022)
The chronicle remained the preferred genre for those dissatisfied with traditional history for a long time, despite a drop in popularity following the Middle Ages. John Galt, a Scottish Romantic writer who is currently experiencing a resurgence of interest from critics, illustrates how the chronicle can be used politically, both in terms of form and content, to help Britain reconcile the material and philosophical advancements of the long eighteenth century with its distant past. Galt's adaptation of the chronicle, in particular, provides a different perspective on the past, one in which history is not seen as something that society must flee or as universally primitive, but rather as a tool to be used to support political systems, a sign of Burkean conservatism's faith in social structures. This line of reasoning exposes a devout Tory who is afraid of the possibility of bloodshed in the post-Revolutionary period, especially political assassination and regicide.